The Relationship Between the Self Control and Self Regulated Learning in Students of the Faculty of Psychology and Educational Sciences at University : Hubungan antara Kontrol Diri dengan Self Regulated Learning pada Mahasiswa Fakultas Psikologi dan Ilmu Pendidikan di Universitas - Dyah Rizqi Nurdiani Fitri; Nurfi Laili (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the relationship between self-control and self-regulated learning in students of the Faculty of Psychology and Education at the University of Muhammadiyah Sidoarjo who have a tendency to have low levels of self-regulated learning. The population in this study were students of the eighth amounting to 463 students and the sample of this study was 210 students who were taken using cluster sampling technique. The data collection technique uses a psychological scale with a likert, namely the self-control scale and a self -regulated learning scale compiled by researchers based on aspects of the scale. The data analysis technique used is the Spearman rho assisted by JASP software. The results of data analysis obtained rxy = 0.694 with a significance value of 0.001 < 0.05, then the proposed hypothesis is accepted, which means that there is a significant positive relationship between self-control and self-regulated learning in eighth semester students of the Faculty of Psychology and Educational Sciences at the University of Muhammaadiyah Sidoarjo. Highlights: Relationship between self-control and self-regulated learning: The study explores the connection between self-control and self-regulated learning in students with low levels of self-regulated learning. Sample and data collection: The study includes 210 eighth-semester students from the Faculty of Psychology and Education at the University of Muhammadiyah Sidoarjo. Data was collected using Likert scales developed by the researchers. Statistical analysis and results: Spearman rho analysis with JASP software revealed a significant positive relationship (rxy = 0.694, p = 0.001) between self-control and self-regulated learning, confirming the proposed hypothesis. Keywords: self-control, self-regulated learning, students, University of Muhammadiyah Sidoarjo, relationship